Manuscripts and Archives Comparative Views on Record-Keeping - Bausi, Alessandro; Brockmann, Christian; Friedrich, Michael (Studies in Manuscript Cultures, 2018)
The series publishes monographs and collective volumes contributing to the emerging field of manuscript studies (manuscriptology), which includes disciplines such as philology, palaeography, codicology, art history, and material analysis. SMC encourages comparative approaches, without geographical or other limitations on the material studied; it contributes to a historical and systematic survey of manuscript cultures, and provides a new foundation for current discussions in Cultural Studies.